Theory of Housing, From Housing, About Housing - Hannu Ruonavaara (Taylor & Francis, 2022)
Four positions concerning theorising housing-related phenomena are discussed. (1) Theory of housing (v1): It is possible and desirable to construct a theory of housing to which all housing-related research topics can be related. (2) Theory about housing: It is not possible, nor desirable to try to construct a theory of housing; one should rather apply theoretical resources developed in established disciplines and research fields in theorising housing-related topics. (3) Theory from housing: It is possible and desirable to theorise housing by scrutinising the nature of housing as a special activity and experience. (4) Theory of housing (v2): It is possible and desirable to construct a theory about the invariable relationships between features of the housing system and features of society. Theory of housing (v1) is shown to be questionable basically due to the fact that housing is not a research topic but a common denominator of various topics. Theory about housing is acceptable with the qualification that housing research can feed back to more general theorising. Theory from housing offers a limited perspective on theorising but it can serve as a necessary check to other theorising. Problems with Theory of housing (v2) have to do with the balance between abstract generalisation and concrete empirical/historical analysis.